Local labor markets and the persistence of population shocks: evidence from West Germany, 1939–1970. (6th September 2020) - Braun, Sebastian T; Kramer, Anica; Kvasnicka, Michael; Meier, Philipp
Abstract: This article studies the persistence of a large, unexpected and regionally very unevenly distributed population shock, the inflow of eight million ethnic Germans from Eastern Europe to West Germany after World War II. Using detailed census data from 1939 to 1970, we show that the shock proved persistent within local labor markets, but was largely reversed between labor markets. These results show that the choice of spatial units can significantly affect the estimated persistence of population shocks. They can thus help to explain why previous studies on the persistence of population shocks reached conflicting conclusions.